Static, Transient and Free Vibirational analysis of thermo magneto electric elastic solid cylinder - Karthikeyan, S; K. Parvatha Varthini, T (International Journal of Engineering and Technology, 2018)
In this paper the static, transient and free vibration analysis of a thermo- magneto-electric-elastic solid cylinder is analyzed stochastically by using hybrid numerical method (combined finite element and Newmark finite difference method).An infinite solid cylinder made up of 6mm class considered. The constitutive equations containing the mechanical, magnetic, electrical and thermal fields and investigated by free and forced Vibirational boundary conditions. The transient finite element equations are obtained by assumed shape functions. After assembling the Mass, Stiffness and Damping and matrices, the global dynamic equations are in the form of time field. The resulting equations are solved by using the finite difference technique with suitable time instants. By using material constants values the displacement, velocity and acceleration of vibrations are obtained with various time values and the non dimensional frequencies are also obtained by different values of non dimensional wave number. Numerical work is carried out by the electric and magnetic materials Cdse and CoFe2o4. The outcomes are tabulated and represented graphically.Â Â